Reference Intervals of Total Testosterone in Adult Filipino Men - Myrna Buenaluz‐Sedurante; Mark Isaiah K. Co; Daryl Jade T. Dagang; Racquel G. Bruno; Annie Jane N. Sarmiento; Michael L. Tee (International Journal of Endocrinology)
Background. The reference range of total testosterone needs to be established locally as ethnic differences in adiposity, insulin sensitivity, and sex hormone-binding globulin (SHBG) levels may affect total testosterone levels. The aim of this study is to establish the reference intervals of total testosterone from healthy, young adult Filipino males. Methods. The study included 110 healthy, Filipino male volunteers aged 21–40, studying or working at the University of the Philippines Manila. Clinical history, height, weight, body mass index (BMI), and blood pressure (BP) were obtained, and blood for total testosterone, SHBG, albumin, insulin, fasting blood sugar (FBS), and total cholesterol was collected. Free testosterone was calculated using Vermeulen’s formula. The 2.5th to 97.5th percentiles of subjects for total testosterone were used as the normative range for Filipino men. Results. The reference range of total testosterone is 7.33–53.01 nmol/L. Conclusion. The present study derived reference ranges of total testosterone using data from apparently healthy, young adult men to support clinical services.